2022
DOI: 10.1111/jcal.12735
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting learning tactics in MOOC using ordered network analysis

Abstract: Background: Select and enact appropriate learning tactics that advance learning has been considered a critical set of skills to successfully complete highly flexible online courses, such as Massive open online courses (MOOCs). However, limited by analytic methods that have been used in the past, such as frequency distribution, sequence mining and process mining, we lack a deep, complete and detailed understanding of the learning tactics used by MOOC learners.Objectives: In the present study, we proposed four m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Due to the unique affordances of unifying descriptions and quantitative representation, QE has a rising interest in learning analytics. For example, Epistemic Network Analysis models behaviors captured in learning environments connected via temporal co-occurrence, which supports interpretations of learner strategy differences and their relationship to outcomes [12,15,48]. For example, Fougt et al [15] distinguish student proficiency levels in higher education writing assessment to support grading via keywords.…”
Section: Quantitative Ethnography Methods In Learning Analyticsmentioning
confidence: 95%
“…Due to the unique affordances of unifying descriptions and quantitative representation, QE has a rising interest in learning analytics. For example, Epistemic Network Analysis models behaviors captured in learning environments connected via temporal co-occurrence, which supports interpretations of learner strategy differences and their relationship to outcomes [12,15,48]. For example, Fougt et al [15] distinguish student proficiency levels in higher education writing assessment to support grading via keywords.…”
Section: Quantitative Ethnography Methods In Learning Analyticsmentioning
confidence: 95%
“…To build a reliable and valid process library, we had initially harnessed the SRL processes based on Bannert's SRL coding protocol (Bannert, 2007), and then included additional relevant processes from several related studies (e.g., Fan et al., 2021; Fan, Lim et al 2022; Kizilcec et al, 2017; Saint et al, 2021, 2020; Siadaty et al, 2016). As a result, we developed the process library shown in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…For example, based on MOOC learners' navigational logs, Matcha et al (2019) detected different learning tactics and learning strategies by identifying clusters of similar SRL behaviours of learners; Rakovic et al (2022) unobtrusively measured metacognitive processes using learners' trace data during a multi‐source writing task (e.g., mouse clicks and keyboard strokes) and used features extracted from these trace data to investigate how SRL processes are associated with the quality of a written product; Fan et al. (2022) used eye‐tracking, mouse movement, and keystroke data as additional data channels to improve the recording of learning actions (e.g., learner's interactions with certain learning tools) and detect SRL processes (e.g., monitoring and evaluating processes during learning) while enhancing the granularity of the measurement; Fan et al. (2022) concluded that eye‐tracking data is particularly valuable for measuring and extracting SRL processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co‐temporal characteristics refer to multiple events co‐occurring within a window, regardless of in which order (Hadwin, 2021). In contrast, sequential characteristics, also named temporal order, are concerned with the order of multiple events in time (Chen et al, 2018; Fan, Tan, et al, 2022). Examples are patterns of ordered actions that frequently occur during an educational game.…”
Section: Literature Reviewmentioning
confidence: 99%